Lorenzo Vicente, J. A. (2001). La formación del profesorado de Enseñanza Media en España (1936-1970). Madrid: Editorial Complutense. - Bartolomé Martínez, Bernabé (Revista Complutense de Educación, 2002)
Sin resumen